The impact of alcohol management practices on sports club membership and revenue. (13th April 2016) - Wolfenden, L.; Kingsland, M.; Rowland, B.; Dodds, P.; Sidey, M.; Sherker, S.; Wiggers, J.
Abstract : Issue addressed: The aim of this study was to assess the impact of an alcohol management intervention on community sporting club revenue (total annual income) and membership (number of club players, teams and spectators). Methods: The study employed a cluster randomised controlled trial design that allocated clubs either an alcohol accreditation intervention or a control condition. Club representatives completed a scripted telephone survey at baseline and again 3 years following. Demographic information about clubs was collected along with information about club income. Results: Number of players and senior teams were not significantly different between treatment groups following the intervention. The intervention group, however, showed a significantly higher mean number of spectators. Estimates of annual club income between groups at follow‐up showed no significant difference in revenue. Conclusions: This study found no evidence to suggest that efforts to reduce alcohol‐related harm in community sporting clubs will compromise club revenue and membership. So what?: These findings suggest that implementation of an intervention to improve alcohol management of sporting clubs may not have the unintended consequence of harming club viability. Abstract : This study investigates the impact of implementing alcohol management practices in community sporting clubs on club revenue and membership. Sports clubs were randomised to receive an intervention to improve alcohol management or a no‐intervention control. At follow‐up, there were significantly more spectators attending intervention clubs, relative to control clubs. There was no significant difference in club income between groups.